Risk Assessment of Toxic Metals from Drinking Water of Taluka Ghorābāri, Sindh, Pakistan - Abdul Raheem Shar; Ghulam Qadir Shar; Zulfiqar Ali Jumani; Aslam Khan Pathan; Zubeda Bhatti; Ali Raza Rind; Ghulam Mujtaba Jogi (Universitas Gadjah Mada, 2022)
In the current study, the quality of groundwater used for drinking purposes was assessed in Taluka Ghorābāri, Sindh, Pakistan. Twenty-five sampling locations were selected for the collection of groundwater. Samples were analyzed for physicochemical and heavy metal analysis, followed by standard methods. Detection of heavy metals was conducted using Atomic Absorption Spectrophotometer. Heavy metals which exceeded the WHO safe limit included Cr (28%), Fe (16%), Mn (48%), and Ni (16%) from the drinking water of the study area. The Cu and Zn were found within the safe limit in all drinking water samples of the study area. The Daily Intake of heavy Metals (DIM) and Health Risk Indexes (HRI) Assessments were calculated to determine risk assessments; the order of mean DIM values was observed as Ni > Cu > Fe > Zn > Cr while HRI was observed in the order of Cu > Mn > Zn > Fe > Cr. The HRI values were observed less than one for both adults and children, which shows the lack of possible health hazards for the people of the study area.